Evaluation of dislocation resistance of three different resin-based root canal sealers from radicular dentin -An ‘in vitro’ study. - Vishnoi, Suchita; Raisingani, Deepak; Prasad, Ashwini. B; Srivastava , Harshit; Jain, Rimjhim; Singh, Anubha (UNIVERSITY JOURNAL OF DENTAL SCIENCES, 2022)
Aim: The aim of this study is to evaluate the dislocation resistance of three different resin-based root canal sealers from radicular dentin -An ‘in vitro’ study. Methodology: Sixty extracted human maxillary canines were sectioned transversally below the cement-enamel junction to obtain 2-mm-thick dentin disks that were randomly divided into three groups (n = 20) for treatment with one of three different root-canal sealers (AH Plus [Dentsply DeTroy, Germany], Bioseal (Equinox Holland), EndoREZ [Ultra dent]). Standardized cavities were prepared to simulate root canals, cavities were filled with sealer material, and push-out bond-strength testing was performed using a universal testing machine. Result: In the present study amongst all the three sealers tested viz AH Plus, EndoREZ & Bioseal. EndoREZ (Group III) goes most superior (14.97 ± 3.17 MPa), followed by AH Plus (Group II) (13.29 ± 2.27 MPa) & the least bond strength was seen with Bioseal (Group I) (4.83 ± 1.62 MPa). There was a gradual decrease in bond strength from a coronal third of radicular dentin to the middle third followed by an apical third in all three groups. Conclusion: Amongst all the three-sealer tested EndoREZ® gave the maximum bond strength, followed by AH Plus® & then Bioseal. Bioseal gave the least bond strength irrespective of the area in radicular dentin. There was a gradual decrease in bond strength from the coronal third of radicular dentin to the middle third followed by an apical third in all three groups.